The Role of Audit In Small And Medium Enterprises - Kelly Kelly; Jessy Venessa; Vivin Vivin (LAFADZ JAYA Publisher, 2023)
Small and Medium Enterprises (SMEs) play a significant role in supporting the economic development of countries, including Indonesia. In 2019, SMEs has reached 63,95 million units which took over 99,62% of all businesses in Indonesia. SMEs also have contributed 61.79% to Indonesia’s Gross Domestic Product in 2020, hence making them an important contributor to the country’s economic growth. However, SMEs hold some weaknesses compared to large and modern businesses which its limited financial condition and difficulties when applying for funding to the bank due to their lack of proper reporting financial statements in accordance with the accounting standards. In order to resolve this issue, the role of independent auditors holds essential part in making SMEs more bankable by auditing their financial statements. Therefore, the financial statement of SMEs will be more reliable so that the bank will approve SMEs credit application.